Fun Learning: Alternatif Metode Bimbingan Belajar Bahasa Inggris Bagi Peserta Didik Level Sekolah Dasar - Istiqomah Nur Rahmawati; Karinda Salsabilla (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The choice of an effective pedagogical strategy is critical in evoking children's participation in the learning process and achieving the intended educational objectives. In the post-pandemic age, the educational landscape has undergone major change, with a trend toward online learning modes accessible via mobile devices. This is made possible through a variety of digital platforms, such as Zoom Meeting, Google Meet, and other similar applications meant to support instructional activities. The lack of direct teacher-child engagement during the learning process has the potential to reduce children's interest in learning, particularly in the setting of elementary school (ES) instruction. The current community service project entailed the development of a service team that designed a work program based on mentoring elementary school pupils in Gedong Pakuon, Bandarlampung. The team's pedagogical approach emphasised delightful and engaging learning experiences. The goal of this initiative is to increase children's interest in English language acquisition while also achieving educational goals on hitherto undiscovered topic matter. The research methodology used is experimental in nature, and the effectiveness of the fun learning approach in increasing children's interest in learning is noticed. The current study's findings show a significant increase in children's participation in knowledge acquisition during the period of program implementation. Furthermore, the study demonstrates that the achievement of learning objectives was effective. Specifically, the ability of youngsters to pronounce vocabulary items and basic sentences relevant to learning materials is a goal.